2021
DOI: 10.3389/fpsyg.2021.641471
|View full text |Cite
|
Sign up to set email alerts
|

Looking for Image Statistics: Active Vision With Avatars in a Naturalistic Virtual Environment

Abstract: The efficient coding hypothesis posits that sensory systems are tuned to the regularities of their natural input. The statistics of natural image databases have been the topic of many studies, which have revealed biases in the distribution of orientations that are related to neural representations as well as behavior in psychophysical tasks. However, commonly used natural image databases contain images taken with a camera with a planar image sensor and limited field of view. Thus, these images do not incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that these statistics are relatively robust with regard to the specific methods they were measured with and the image content of the natural scenes they were computed for, showing characteristic peaks at both cardinal orientations (Coppola et al, 1998; Girshick et al, 2011; Wang et al, 2016). However, outdoor scenes containing fewer man-made objects typically show less pronounced peaks at the cardinals compared to indoor scenes (Coppola et al, 1998; Straub and Rothkopf,2021) (see Supplementary Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that these statistics are relatively robust with regard to the specific methods they were measured with and the image content of the natural scenes they were computed for, showing characteristic peaks at both cardinal orientations (Coppola et al, 1998; Girshick et al, 2011; Wang et al, 2016). However, outdoor scenes containing fewer man-made objects typically show less pronounced peaks at the cardinals compared to indoor scenes (Coppola et al, 1998; Straub and Rothkopf,2021) (see Supplementary Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, outdoor scenes containing fewer man-made objects typically show less pronounced peaks at the cardinals compared to indoor scenes (Coppola et al, 1998;Straub and Rothkopf, 2021) (see Supplementary Fig. 2).…”
Section: θ *mentioning
confidence: 99%
“…Incorporating topographic variations in feature encodings may allow neural networks to access priors contained in natural “embodied” visual experience ( Mineault et al, 2021 ), built over million years of species-specific evolution. This would not only bring in silico models closer in line with in vivo visual systems, but it may also bridge the gap between species-specific visual inputs and artificial training sets, which lack the structure of natural embodied visual experience ( Straub and Rothkopf, 2021 ). Alternatively, the use of more naturalistic “animal-view” movies as input ( Betsch et al, 2004 ), coupled with architectural flexibility, may allow neural networks to learn topographic specializations predictive of patterns in the retina or other hierarchical layers of the visual system ( Doshi and Konkle, 2021 ; Blauch et al, 2022 ).…”
Section: Implications For Future Studies Of the Visual Systemmentioning
confidence: 99%
“…Finding the underlying design principles which allow humans to adaptively find and select relevant information (Tistarelli and Sandini, 1993 ; Findlay and Gilchrist, 2003 ; Krause and Guestrin, 2007 ; Friston et al, 2015 ; Ognibene and Baldassare, 2015 ; Bajcsy et al, 2017 ; Jayaraman and Grauman, 2018 ; Ballard and Zhang, 2021 ) is important for Robotics and related fields (Shimoda et al, 2021 ; Straub and Rothkopf, 2021 ). Active inference, which has recently become influential in computational neuroscience, is a normative framework proposing one such principle: action, perception, and learning are the result of minimization of variational free energy, a form of prediction error.…”
Section: Applying Principles Of Active Vision and Perception To Roboticsmentioning
confidence: 99%